Not being able to speak is torture: performing listening to painful narratives - Sotelo Castro, Luis Carlos (International journal of transitional justice, 2020)
This Note discusses a new creative approach to intervene in the interaction between survivors who contribute their memories of a painful past and the public they want to reach. It proposes that by turning both the narrator and the public into performers of listening, they are placed in a relational context that offers an alternative space in which victims’ and the public’s memories, emotions and thoughts in a transitional context can be worked through. The method thereby corrects the notion of the public as a disembodied, virtual totality underlying state-led transitional justice institutions.